Bagaimana Self Disclosure pada Persahabatan Remaja Beda Agama? - Aisyah, Sekar; Wulandari, Dyah Astorini; Rahardjo, Pambudi; Septiningsih, Dyah Siti (Universitas Muhammadiyah Purwokerto, 2023)
This study explores self-disclosure among adolescents engaged in interfaith friendships. Utilizing a qualitative case study approach, data were collected through interviews with four purposively sampled adolescent females. Analytical techniques included pattern matching, expansion generation, and time series analysis, with source triangulation employed to ensure credibility. The study identified five main themes of self-disclosure in these interfaith friendships: honesty, accuracy, amount, frequency and duration, depth, intent, and the positive-negative nature. Additional themes included the process of self-disclosure, the duration of the friendship, trust, tolerance, and joint activities. The findings suggest that self-disclosure in interfaith adolescent friendships involves sharing and learning about each other's religions, which fosters greater appreciation and tolerance of religious diversity. Future research should examine the long-term effects of self-disclosure in interfaith friendships on adolescents' social and psychological well-being.